General Modeling Framework for Transmissible Diseases - ROJAS, OSCAR FRANCISCO; CUMSILLE, PATRICIO; CONCA, CARLOS (Usach, 2025)
Data and Source Codes of the General Modeling Framework for Transmissible Diseases.
GMF-TD
Matlab, 2024a
Keywords: Matemáticas; Ciencias de la Información y Computación; Ciencias Biológicas; Ciencias de la Salud; Applied mathematics; Epidemiology